Analysis Of Archives Digitalization System Management In Lldikti Region Iii Jakarta - Baringbing, Rizki; Marsofiyati; Maulida, Ervina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research used a qualitative descriptive method which was carried out with the aim of finding out more about the management of the archive digitization system at LLDikti Region III Jakarta. Data collection techniques use observation, interviews, and documentation and are obtained from previous research, articles, books, andw ebsites related to research on archival digitization system management.